Child transmission of SARS-CoV-2: a systematic review and meta-analysis - Sarah L Silverberg; Bei Yuan Zhang; Shu Nan Jessica Li; Conrad Burgert; Hennady P Shulha; Vanessa Kitchin; Laura Sauvé; Manish Sadarangani (BMC, 2022)
Abstract Background Understanding of the role of children in COVID-19 transmission has significant implications for school and childcare policies, as well as appropriate targeting of vaccine campaigns. The objective of this systematic review was to identify the role of children in SARS-CoV-2 transmission to other children and adults. Methods MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, and Web of Science were electronically searched for articles published before March 31, 2021. Studies of child-to-child and child-to-adult transmission and quantified the incidence of index and resulting secondary attack rates of children and adults in schools, households, and other congregate pediatric settings were identified. All articles describing confirmed transmission of SARS-CoV-2 from a child were included. PRISMA guidelines for data abstraction were followed, with each step conducted by two reviewers. Results 40 of 6110 articles identified met inclusion criteria. Overall, there were 0.8 secondary cases per primary index case, with a secondary attack rate of 8.4% among known contacts. The secondary attack rate was 26.4% among adult contacts versus 5.7% amongst child contacts. The pooled estimate of a contact of a pediatric index case being infected as secondary case was 0.10 (95% CI 0.03-0.25). Conclusions Children transmit COVID-19 at a lower rate to children than to adults. Household adults are at highest risk of transmission from an infected child, more so than adults or children in other settings.